Sudden Stops in Capital Inflows: Global Drivers, Domestic Risks, and Macroeconomic Consequences in Emerging Markets - Diaz, Luis; Collin, Gregory (Journal of Business and Economic Options, 2025)
This article investigates the principal drivers of abrupt cessations in several classes of gross capital inflows and evaluates their macroeconomic consequences for economies characterised as emerging markets. Using a complementary log–log hazard model, the analysis isolates the variables that precipitate sudden stops and distinguishes between external influences and domestic circumstances. Results indicate that while local fundamentals such as exchange rate regimes, reserve adequacy, and fiscal balance exert influence, global forces remain pre-eminent. In particular, shifts in worldwide risk sentiment, heightened uncertainty, and contagion originating from peer economies significantly elevate the hazard of a capital-flow interruption. The study further shows that an excessive concentration of short-term capital raises vulnerability, yet strong institutional frameworks moderate this specific risk, underscoring the protective role of governance quality. Turning to outcomes, the evidence reveals that sudden stops linked to debt-financed inflows inflict especially severe real and financial costs: output contracts more sharply, current-account adjustments become abrupt, and asset prices experience deeper declines when compared with interruptions associated with equity or direct investment. These findings imply that policy efforts should not only address global push factors through prudent reserve management and macroprudential buffers but also improve institutional resilience to limit the incidence and impact of short-term, debt-driven surges. Robust data transparency can temper investor panic during global volatility episodes. Overall, the study clarifies the relative importance of international shocks versus domestic policies in shaping sudden-stop dynamics and emphasises the disproportionately negative consequences of debt-based reversals.